Kesalahan Penulisan pada Pamflet dan Papan Nama Pertokoan di Kota Baturaja Kabupaten OKU - Nur Aisyah; Lifa Zahara; Nurhayati Nurhayati; Ratu Wardarita (Jurnal Lentera Pedagogi, 2020)
This study aimed to illustrate language errors in writing pamphlets and signage for shops. Samples were taken in the town of Baturaja Ogan Komering Ulu Regency. This paper is a descriptive study focused on extracting qualitative data, with the hope that a more detailed and detailed picture of the research object will be obtained. From the results of this study, in general it can be said that errors in the Indonesian language in writing pamphlets and signboard shops are still often found that are not in accordance with good and correct Indonesian language rules. Writing errors in pamphlets and signboard shops are caused by the influence of the use of everyday language or writing written based on oral speech, limited knowledge of the rules of the Indonesian language, as well as a tendency to merely imitate. In addition, people also ignore the use of language in the correct writing, so that the error has the potential to trigger the problem of language errors in writing pamphlets and signage for shops.